Systematics and biogeography of the spider genus Mallinella Strand, 1906, with descriptions of new species and new genera from Southeast Asia (Araneae, Zodariidae) - Dankittipakul, Pakawin; Jocqué, Rudy; Singtripop, Tippawan (Zootaxa, 2012)
The systematics status of the spider genus Mallinella Strand, 1906 (Araneae, Zodariidae), the phylogenetic relationshipof the species within the genus and its relationships to other zodariids were investigated by means of cladistic analysis ofmorphological data. Mallinella is redefined and characterized by a single synapomorphy: the presence of posterior ventralspines situated in front of the spinnerets arranged in a single row. The genus is clearly palaeotropical, occurring in Africa,Indian subcontinent, Indo-Burma, Sundaland, Wallacea and Polynesia-Micronesia.Two hundred and two (202) Mallinella species are treated. One hundred and one (101) species are described as newand placed in twenty-two (22) species-groups, making Mallinella the largest zodariid genus. Nineteen (19) species are redescribed, the conspecific sex of seven (7) species is discovered and described for the first time. Fifteen (15) new com-binations are proposed. Nine (9) Storena species are here transferred to Mallinella: M. beauforti (Kulczyński, 1911) comb.nov., M. sciophana (Simon, 1901) comb. nov., M. sobria (Thorell, 1890) comb. nov., M. fasciata (Kulczyński, 1911)comb. nov., M. vicaria (Kulczyński, 1911) comb. nov., M. redimita (Simon, 1905) comb. nov., M. melanognatha (van Has-selt, 1882) comb. nov., M. nilgherina (Simon, 1906) comb. nov., M. vittata (Thorell, 1890) comb. nov. Two Storena spe-cies are transferred to Asceua: A. dispar (Kulczyński, 1911) comb. nov., A. quinquestrigata (Simon, 1905) comb. nov. OneStorena species is transferred to Oedignatha (Liocranidae): O. aleipata (Marples, 1955) comb. nov. One Storena speciesis transferred to Cybaeodamus: C. lentiginosus (Simon, 1905) comb. nov. Storena tricolor Simon, 1908 is transferred tothe Asteron complex of Australia. Three Storena and two Mallinella species are misplaced; they belong to undescribedgenera (S. kraepelini Simon, 1905; S. lesserti Berland, 1938; S. parvula Berland, 1938; M. khanhoa Logunov, 2010; M.rectangulata Zhang et al., 2011). Mallinella vittata (Thorell, 1890) comb. nov. is revalidated and removed from the syn-onymy with M. zebra (Thorell, 1881). Storena vittata Caporiacco, 1955 is removed from homonym replacement (S. ca-poriaccoi Brignoli, 1983) with S. vittata Thorell, 1890 (= M. vittata comb. nov.). Storena annulipes Thorell, 1892 isremoved from its preoccupied name with S. annulipes (L. Koch, 1867) in Storena and transferred to Mallinella; its re-placement name S. cinctipes Simon, 1893 is suppressed.Zodarion luzonicum Simon, 1893, Storena multiguttata Simon, 1893, S. semiflava Simon, 1893 and S. obnubila Si-mon, 1901 are regarded as nomina dubia. Six Indian species were misplaced in Storena; they belong to one of the follow-ing genera: Mallinella, Heliconilla gen. nov., Workmania gen. nov., Heradion, or Euryeidon. These taxa are S. arakuensisPatel & Reddy, 1989, S. debasrae Biswas & Biswas, 1992, S. dibangensis Biswas & Biswas, 2006, S. gujaratensis Tikader& Patel, 1975, S. indica Tikader & Patel, 1975 and S. tikaderi Patel & Reddy, 1989. They are regarded as species incertaesedis.A new genus, Heliconilla gen. nov., is proposed for nine species, six of which are new to science while the otherthree are transferred from Mallinella and Storena. These taxa are: H. irrorata (Thorell, 1887) comb. nov., H. oblonga(Zhang & Zhu, 2009) comb. nov., H. thaleri (Dankittipakul & Schwendinger, 2009) comb. nov.Workmania gen. nov. is established to accommodate two species from Southeast Asia; W. juvenca (Workman, 1896)comb. nov. is transferred from Storena.It is unlikely that the origin of Mallinella dates back more than 100 MYA. Mallinella or its ancestor is believed tohave evolved during the Cretaceous, after the separation of South America from Gondwana, and the greater part of itsevolution took place during the Tertiary. The Asian-Australian lineages of Mallinella could migrate to India via GreaterSomalia before or after the K-T extinction (65 MYA), before the Indian subcontinent joined Asia (ca. 45 MYA).The bio-geographic history of the genus involves plate tectonics during the Cretaceous and the Cenozoic in combination with cli-matic changes and alternating climatic cycles which might have led to episodes of range expansion, isolation of populations and allopatric speciation.